The Effect of Android-Based SDIDTK Applications on The Implementation of SDIDTK - windiiyani, winda; Susilawati, Sri; Rismayanti, Tanti (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
The growth and development of children 0-5 years or more is often referred to as the golden period where this period is a period of growth and development of children that will not be repeated. At the age of toddlers, children are very sensitive to the environment because at this time it takes place quickly. The occurrence of deviations from growth and development at this time cannot be overcome and will even be difficult to repair Objectives: The purpose of this study is to analyze the effect of the SDIDTK application on the implementation of SDIDTK in the work area of the Kersanegara Health Center, Tasikmalaya City 2020. This study uses an analytical observational method, with an analytical approach. Cross sectional which aims to find a causal relationship between variables. All variables were measured at the same time. Sampling by accidental sampling. A total of 33 respondents. The results showed that there was an effect of the SDIDTK application on the implementation of SDDITK. The conclusion revealed that the SDIDTK application had an effect on the implementation of SDIDTK.